RANCANG BANGUN MESIN PENGHALUS TANAH DAN PENCETAK BATA MERAH KHUSUS INDUSTRI MIKRO - Akmal Haidar Derry Farras; Fais Hamzah; Tri Andi Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Abstract – The red brick manufacturing industry is starting to be abandoned by many people and switch to using hebel bricks. Several things have caused red bricks to be abandoned, namely the price of red bricks is more expensive when compared to lightweight bricks for a size of 1 m2, besides that red bricks produced by conventional production processes have a red brick surface shape that is often uneven. Based on these conditions, we need an idea and innovation to create a machine to improve the production of red bricks in the form of a machine for smoothing and molding the clay of red brick for home-scale industries. The machine manufacturing process will use the Ulrich method from identifying machine requirements to selecting concepts and fabrication. Based on the results of the design using the Ulrich method, the design concept was chosen 1. Then planning, calculation and analysis will be carried out to determine the components to build the machine. The next stage is making of detailed drawings of the machine, followed by the fabrication and testing process. In testing clay smoothing and molding machine for red brick, the machine is capable of producing 120 red bricks per hour with a total cost of Rp. 12.217.500,-.